2016
DOI: 10.1016/j.clinph.2015.04.291
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of infant cortical synchrony is constrained by the number of recording electrodes and the recording montage

Abstract: Dense array EEG Connectivity Brain development h i g h l i g h t sAnalysis of brain connectivity from the neonatal EEG is strongly enhanced by adding the number of electrodes. Sensitivity and specificity of cortical synchrony estimates depend on the analysis montage; average and Laplacian montage have the best performance. The number of electrodes defines the optimal montage and it also sets the limits for the level of analytic details. a b s t r a c tObjective: To assess how the recording montage in the neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 71 publications
0
29
0
Order By: Relevance
“…EEG phase differences are often used to investigate “inter-sites phase synchronization”, which is an estimation of the connectivity between two EEG electrode sites (van Mierlo et al, 2014 ; Kang et al, 2015 ; Tokariev et al, 2016 ). Phase locking value (PLV; Lachaux et al, 1999 ) is a possible means to represent the synchronization phenomena in EEG signals (Lachaux et al, 1999 ).…”
Section: Methodsmentioning
confidence: 99%
“…EEG phase differences are often used to investigate “inter-sites phase synchronization”, which is an estimation of the connectivity between two EEG electrode sites (van Mierlo et al, 2014 ; Kang et al, 2015 ; Tokariev et al, 2016 ). Phase locking value (PLV; Lachaux et al, 1999 ) is a possible means to represent the synchronization phenomena in EEG signals (Lachaux et al, 1999 ).…”
Section: Methodsmentioning
confidence: 99%
“…This property is generally attributed to the significantly thinner skull bones of the newborn. These studies suggest that by using a high spatial sampling of the scalp EEG and a realistic newborn head model and conductivity values (more than 1 order of magnitude higher than the adult ones) (31, 32), we could compute a reliable source reconstruction of the newborn's EEG (33,34). With these indications, taking advantage of high-density EEG recordings, we estimated the cortical generators of the scalplevel effects with a source localization model based on newborn's realistic anatomical structure and electrical properties (34).…”
Section: Significancementioning
confidence: 99%
“…In addition to the contralateral SER to hand stimulation, we also detected a systematic albeit smaller ipsilateral response (iSER), confirming the prior work of Hrbek et al (). Our extensive theoretical and empiric studies on newborn EEG signals (Gargiulo, Belfiore, Friethgeirsson, Vanhatalo, & Ramon, ; Odabaee, Freeman, Colditz, Ramon, & Vanhatalo, ; Odabaee et al, ; Tokariev, Vanhatalo, & Palva, ), including works on conventional evoked potentials (Nevalainen et al, ) in term infants, have shown that newborn scalp EEG signal is spatially very specific. Hence, the present results cannot be explained by spatial smearing of cortical signals akin to what is commonly seen in the adult scalp EEG studies.…”
Section: Discussionmentioning
confidence: 99%